The Effects of Erotic Capital on Occupational Selection A Comparison between Men and Women - Zhang, Yi (Chloe) (Advances in Social Sciences Research Journal, 2017)
This paper examines erotic capital’s effect, a composite measure of beauty, personality, grooming, shape, liveliness and sexuality, on occupational selection between 1994 and 2009 by estimating a multinomial logistic model using the National Longitudinal Study of Adolescent Health (Add Health). My results find a different effect of erotic capital between men and women. In particular, beauty and grooming show a partial significant influence on women’s occupational selection. The combined effect of six types of erotic capital is also substantially significant for women. This paper contributes to the occupational choice literature by providing evidence of the importance of erotic capital accumulation to women’s career attainment.